Knowledge regarding emergency management of avulsed teeth among elementary school teachers in Jaboatão dos Guararapes, Pernambuco, Brazil - A de Lima Ludgero; T de Santana Santos; A V Fernandes; D G de Melo; A C Peixoto; F A da Costa Araújo; A T Dourado; ACA Gomes (Wolters Kluwer Medknow Publications, 2012)
Objective: The purpose of the present study was to assess the knowledge regarding emergency management of tooth avulsion among elementary schoolteachers in the city of Jaboatão dos Guararapes, Pernambuco, Brazil. Materials and Methods: A total of 338 teachers answered a questionnaire with items on emergency procedures following tooth avulsion. Results: The majority of teachers (89.1%) had received no previous orientation regarding management of dental trauma and 81.4% had not witnessed an accident in which tooth avulsion had occurred. If an avulsed tooth had fallen to the ground, 84.3% of the teachers said they would pick it up, and 67.8% of them stated that they would clean it with water or some other liquid. A total of 33.1% said that they would take the student with the tooth in hand to a dental office. Of the respondents 88.5% would seek professional help immediately; 85.2% stated they would be unable to reimplant the avulsed tooth; and 39.3% would store the tooth in water. Conclusions: A lack of technical information was observed among teachers regarding management of tooth avulsion. Educational campaigns at schools are necessary to modify the behavior of the teachers with regard to management of tooth avulsion. Further studies should be carried out for the assessment of teachers who have participated in educational campaigns to make the treatment of dental trauma a matter of public interest.